CRISPR/Cas9-Induced Loss-of-Function Mutation in the Barley Mitogen-Activated Protein Kinase 6 Gene Causes Abnormal Embryo Development Leading to Severely Reduced Grain Germination and Seedling Shootless Phenotype - Křenek, Pavel; Chubar, Elizaveta; Vadovič, Pavol; Ohnoutková, Ludmila; Vlčko, Tomáš; Bergougnoux, Véronique; Cápal, Petr; Ovečka, Miroslav; Šamaj, Jozef (Frontiers in Plant Science, 2021)
The diverse roles of mitogen-activated protein kinases (MAPKs, MPKs) in plant development could be efficiently revealed by reverse genetic studies. In Arabidopsis, mpk6 knockout mutants complete the life cycle; however, ~40% of their embryos show defects in the development leading to abnormal phenotypes of seeds and seedlings' roots. Contrary to the Arabidopsis MPK6, the rice MPK6 (OsMPK6) is an essential gene as transfer DNA (T-DNA) insertion and CRISPR/Cas9 induced loss-of-function mutations in the OsMPK6 cause early embryo arrest. In this study, we successfully developed a viable transgenic barley line with the CRISPR/Cas9-induced heterozygous single base pair cytosine-guanine (CG) deletion [wild type (WT)/−1C] in the third exon of the HvMPK6 gene, a barley ortholog of the Arabidopsis and rice MPK6. There were no obvious macroscopic phenotype differences between the WT/−1C plants and WT plants. All the grains collected from the WT/−1C plants were of similar size and appearance. However, seedling emergence percentage (SEP) from these grains was substantially decreased in the soil in the T2 and T3 generation. The mutation analysis of the 248 emerged T2 and T3 generation plants showed that none of them was a biallelic mutant in the HvMPK6 gene, suggesting lethality of the −1C/−1C homozygous knockout mutation. In the soil, the majority of the −1C/−1C grains did not germinate and the minority of them developed into abnormal seedlings with a shootless phenotype and a reduced root system. Some of the −1C/−1C seedlings also developed one or more small chlorotic leaf blade-like structure/structures. The −1C/−1C grains contained the late-stage developed abnormal embryos with the morphologically obvious scutellum and root part of the embryonic axis but with the missing or substantially reduced shoot part of the embryonic axis. The observed embryonic abnormalities correlated well with the shootless phenotype of the seedlings and suggested that the later-stage defect is predetermined already during the embryo development. In conclusion, our results indicate that barley MPK6 is essential for the embryologically predetermined shoot formation, but not for the most aspects of the embryo and early seedling development.